Actor' interaction in the follow-up on performance auditing issues in Malaysia: Uncovering the contributing factors and constraining challenges - Umor, Sarimah; Zakaria, Zarina; Sulaiman, Noor Adwa; Kutty, Rasheed Mohamed (Science Publishing Corporation, 2018)
This paper explores the extent and nature of actors' interaction in follow-up on performance auditing issues with the attempt to uncover the contributing factors as well as constraining challenges from the Malaysian public sector audit perspectives. Fifty five (55) semi structured interviews data derived from snowball purposive sampling and governance network theory as underlying theory are employed to analyze the data based on subjective qualitative approach. The overall results indicate that interaction has an impact on key actors' involvement in the follow-up practice. The responses gathered from the interviewees demonstrate that involvement of key actors are more important with some other possible factors. Based on the above situation, this paper argued, effective communication and engaging right authority or external actors are important in enhancing the effectiveness of follow-up practice. The findings suggest, audit institution need to make more key actors to involve in order to solve complex audit issues, particularly the regulators such as enforcement agencies. The regulator expects and hope the auditors to share important first-hand information about audit issues as soon as possible. For regulators, early involvement considered more appropriate. Regulators want to secure sufficient evidence so that further investigation and action can be taken so as not to lose important evidence and avoid dealing with outdated issues. Actors' involvement by means of interaction are timely and should be enhanced in terms of information sharing and overcoming problem related to actor role and involvement. This is the first study that employed governance network theory to explore the nature and extent of follow-up on performance auditing issues involving various actors' interaction in the public sector audit environment.